Anthocyanin stability: a chemometrical approach - Cabrita, Luís (2011)
The stability of cyanidin 3-glucoside towards five different factors (pH, anthocyanin concentration, sodium chloride concentration, ascorbic acid concentration, Oxygen) was studied during 60 days storage at room temperature using a 2^4-1 reduced factorial design. The influence of each individual parameter on anthocyanin stability was found to vary as a function of time. Sodium chloride and ascorbic acid were, respectively, the variables most contributing to and against anthocyanin stability. Results suggest there may be some degree of interaction between anthocyanin/ascorbic acid, and between pH/Oxygen, affecting anthocyanin degradation.